Monocarboxylate-driven structural growth in Calix[n]arene-polyoxotitanate hybrid systems: utility in hydrogen production from water. Issue 90 (26th October 2020) - Yang, Xin-Xue; Yu, Wei-Dong; Yi, Xiao-Yi; Li, Lei-Jiao; Liu, Chao
Abstract : A carboxylate-driven assembly strategy has been developed for the first time to build calix[ n ]arene-based polyoxotitanate clusters with tuneable nuclearity and structures. Abstract : A carboxylate-driven assembly strategy has been developed for the first time to build calix[ n ]arene-based polyoxotitanate clusters with tuneable nuclearity and structures. Photocatalytic studies revealed that these clusters exhibit structural-dependent H2 evolution ability with a maximum rate up to 415.11 μmol h −1 g −1, which is almost the highest recorded in polyoxotitanate clusters.